2021
DOI: 10.3390/antibiotics10070852
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles Mediated by Entomopathogenic Fungi: Antimicrobial Resistance, Nanopesticides, and Toxicity

Abstract: Silver nanoparticles are widely used in the biomedical and agri-food fields due to their versatility. The use of biological methods for the synthesis of silver nanoparticles has increased considerably due to their feasibility and high biocompatibility. In general, microorganisms have been widely explored for the production of silver nanoparticles for several applications. The objective of this work was to evaluate the use of entomopathogenic fungi for the biological synthesis of silver nanoparticles, in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 91 publications
0
29
0
Order By: Relevance
“…Also, when leaves infested by Aphis nerii were dipped into various concentrations of NPs, there was a significant effect on their development [24]. Studies have been carried out on the insecticidal effects of silver nanoparticles and have shown that they can manage the insects that damage crops such as Spodoptera littoralis [28]. Another study using biosynthesized AgNPs showed larvicidal toxicity against Anopheles stephensi, Aedes aegypti, and Culex quinquefasciatus [29].…”
Section: Discussionmentioning
confidence: 99%
“…Also, when leaves infested by Aphis nerii were dipped into various concentrations of NPs, there was a significant effect on their development [24]. Studies have been carried out on the insecticidal effects of silver nanoparticles and have shown that they can manage the insects that damage crops such as Spodoptera littoralis [28]. Another study using biosynthesized AgNPs showed larvicidal toxicity against Anopheles stephensi, Aedes aegypti, and Culex quinquefasciatus [29].…”
Section: Discussionmentioning
confidence: 99%
“…Banu and Balasubramanian [29] found the LC 50 value of 0.79 ppm for B. bassiana AgNPs against second instar larvae of Aedes aegypti. Santos et al [50,51] also discussed and elaborated on the synthesis and toxicity of nanoparticles mediated by entomopathogenic fungi. The possible mechanism of action of M. anisopliae-chitosan nanoparticles can be explained by different phenomena or hypotheses, such as: (1) enhanced degradation of the insect cuticle or delayed ecdysis in response to M. anisopliae-chitosan due to a combined action of extracellular hydrolytic enzymes produced by fungi known for their effect on an insect cuticle [41,[52][53][54]; or (2) decreased efficiency to convert the consumed food into a growth and energy source through the possible diversion of energy from growth to the detoxification process [10,.…”
Section: Toxicity Of Chitosan-based Nanoparticles Of Metarhizium Anisopliae Against Plutella Xylostellamentioning
confidence: 99%
“…Therefore, the need for environmentally friendly production of Ag NPs has attracted attention in biogenic approaches. Several microorganisms, such as algae [ 16 ], bacteria [ 17 ] and fungi [ 18 ], have been utilized to demonstrate the use of successful synthesis of Ag NPs that reduces chemical expenses and chemical toxicity, and provides easy extraction. On the other hand, plant-based methods employed in Ag NPs synthesis are among the most widely used biological methods, due to their wide distribution, safe handling, ease of availability, and being a good source of metabolites.…”
Section: Introductionmentioning
confidence: 99%